Kinetic modeling of quality changes of chilled ready to serve lasagna - Olivera, Daniela Flavia (2012)
Pre-cooked pasta, in particular lasagna, plays an important role in the market of chilled ready to serve meals. In this work we analyzed the evolution of the most important physical and sensory quality attributes of lasagna sheets during their refrigerated storage, at 0, 4 and 10°C. The quality of ready meals deteriorates with storage time, and food loses its freshness condition. The same behavior was observed for all analyzed characteristics: as the storage temperature increases, reaction rate (measured by the kinetic constant and activation energy) also increases, confirming the influence of temperature in quality loss. Besides, overall acceptability was the more sensitive attribute to temperature changes, with Q 10 equal to 4, indicating an indirect but strong dependence of consumers' opinion on storage temperature. Finally, shelf life models, based on sensory analysis and on microbial spoilage, were compared, showing that the adopted sensory score determines which criterion is more restrictive. Kinetic data provide a useful tool to control storage, ensuring good safety and sensory quality.